The Recent Convergence of Financial Development in Asia - Robert Dekle; Madhavi Pundit (Asian Development Bank (ADB), 2015)
We construct an index of financial development for 23 Asian economies based on subindices of access, depth, and efficiency of financial institutions and markets and find evidence that economies with weaker financial systems are catching up to the Asian benchmark economies, namely Hong Kong, China; Japan; the Republic of Korea; and Singapore. Gross domestic product (GDP) per capita, aggregate GDP, and mobile subscriptions all increase the growth rate of financial development in Asian economies while institutional factors have insignificant or ambiguous effects. We also evaluate the relative importance of the subindices in delivering high economic growth, low volatility, and greater financial access.
hdl:11540/5083
Keywords: C82; G01; G02; 330; Asian economies; convergence to benchmark; financial development; index construction